Boron Carbon Nitride-Assisted Electro-Functionalization of Screen-Printed Electrode for Tryptophan Sensing - Garg S.; Singh A.; Parmar A.S.; Rosy N. (My University, 2025)
Screen-printed electrodes (SPEs) have emerged as reliable probes for portable, economical, and practical testing platforms in point-of-care (PoC) applications. Compared to the conventional three-electrode systems, SPEs require significantly less sample volume and omit the cleaning and pre-treatment requirements. This work is focused on amplifying the response signal of SPE using a facile protocol for boron carbon nitride (BCN)-assisted SPE surface functionalization using cyclic voltammetry (CV). To validate the success of the modification, the SPE surface is subjected to chemical and electrochemical characterization using X-ray photoelectron spectroscopy, CV, and differential pulse voltammetry. Ascribed to the BCN’s electrocatalytic ability, the modified SPE significantly improves electrochemical activity, with a five-fold increase in current response and an 18 mV potential shift. The fabricated sensing platform demonstrates high sensitivity and selectivity toward quantitative analysis of tryptophan with a detection limit of 36.4 nM. Furthermore, the developed sensor was tested for monitoring TRP levels in complex matrices like food and human body fluids. This proposed approach of electrode modification holds promise for providing swift, precise, and cost-effective means for improving the sensitivity of SPEs for trace level detections required for PoC applications. © 2023 American Chemical Society